Uji Efektivitas Penyembuhan Luka Bakar dari Sediaan Gel Ekstrak Daun Jarak Pagar (Jatropha Curcas L) pada Tikus Putih Jantan (Rattus Norvegicus) - Mesak, Ivan; Christina, Odilia Dea; T.I., Angelina (Jurnal Farmasi & Sains Indonesia, 2024)
The occurrence of burns on the skin is a type of injury that requires fast and appropriate treatment in order to achieve an optimal level of healing. Handling burns using medicinal plants can be done. One of the plants that can be used is Jatropha leaves. Jatropha leaves contain active substances such as saponins, tannins, alkaloids, and flavonoids that are efficacious as antibacterial, antioxidant, anticancer and antiinflammatory. The purpose of this study was to determine the effectiveness of Jatropha curcas leaf extract gel preparations with concentrations of 10%, 15%, 20% on burn wound healing. This study is an experimental study by comparing the effectiveness of burn wound healing in rats in each test group, namely negative control given gel base, positive control given Bioplacenton gel, and three test control groups with each given Jatropha leaf extract gel concentrations of 10%, 15% and 20%. The test results show that the most effective Jatropha leaf extract gel preparation heals rat burns, namely the 20% concentration compared to the positive control with a P>0.914 value (P>0.05).